2006
DOI: 10.1002/qua.21141
|View full text |Cite
|
Sign up to set email alerts
|

Exact analytical solutions to the Kratzer potential by the asymptotic iteration method

Abstract: For any n and l values, we present a simple exact analytical solution of the radial Schrödinger equation for the Kratzer potential within the framework of the asymptotic iteration method (AIM). The exact bound-state energy eigenvalues (E nl ) and corresponding eigenfunctions (R nl ) are calculated for various values of n and l quantum numbers for CO, NO, O 2 , and I 2 diatomic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(151 citation statements)
references
References 13 publications
4
147
0
Order By: Relevance
“…We have shown an alternative method to obtain the energy eigenvalues and corresponding Where there is no such a solution, the energy eigenvalues are obtained by using an iterative approach [18,19,20]. As it is presented, AIM puts no constraint on the potential parameter values involved and it is easy to implement.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown an alternative method to obtain the energy eigenvalues and corresponding Where there is no such a solution, the energy eigenvalues are obtained by using an iterative approach [18,19,20]. As it is presented, AIM puts no constraint on the potential parameter values involved and it is easy to implement.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable interest has recently been shown in the Kratzer-Fues [12,[16][17][18][19] as a model to describe internuclear vibration of a diatomic molecule [20][21][22][23]. This potential can be expressed in the form…”
Section: Potentialsmentioning
confidence: 99%
“…Recently a technique, called the Asymptotic Iteration Method (AIM) has been introduced [1,2] to obtain eigenvalues of second order homogeneous differential equations. In the case of the Schrödinger equation, it has been found that AIM exactly reproduces the energy spectrum for most exactly solvable potentials [2][3][4] and for non-exactly solvable potentials it produces very good results [5][6][7].…”
Section: Introductionmentioning
confidence: 99%